Comparative Evaluation of the Implementation of Simultaneous Village Head Elections in Pandeglang Regency (Case Study in Tegalwangi Village, Menes District and Tegal Cikedal Village, Pandeglang Regency) - Ariyan, Said; Yuslia, Ifa (Lenggogeni Data Publishing, 2025)
This study aims to evaluate the comparison of the implementation of simultaneous village head elections in Pandeglang Regency, focusing on two villages, namely Tegalwangi Village, Menes District and Tegal Cikedal Village, Pandeglang Regency. This study examines the extent of effectiveness, community participation, as well as driving and inhibiting factors in the village head election process in the two regions. The study uses William N. Dunn's evaluation theory as an analytical framework, with a qualitative descriptive method. Data was collected through interviews, observations, and documentation of ten key informants directly involved in the implementation of the village head election. Data analysis was carried out using the Miles and Huberman interactive model which included data reduction, data presentation, and conclusion drawn. The results of the study show that the implementation of simultaneous village head elections in Pandeglang Regency is generally going well and democratically, reflected in the increase in community participation and acceptance of the election results. However, it was found that there are potential obstacles such as the practice of black campaigns that still occur in several village head candidates. Therefore, it is necessary to increase supervision and enforcement of rules to ensure that the implementation of the next village head election runs more transparently, honestly, and with integrity.